2020
DOI: 10.1016/j.ajem.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic manifestations and complications of COVID-19

Abstract: The novel coronavirus disease of 2019 (COVID-19) is associated with significant morbidity and mortality. While much of the focus has been on the cardiac and pulmonary complications, there are several important dermatologic components that clinicians must be aware of. Objective: This brief report summarizes the dermatologic manifestations and complications associated with COVID-19 with an emphasis on Emergency Medicine clinicians. Discussion: Dermatologic manifestations of COVID-19 are increasingly recognized w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
123
1
41

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(168 citation statements)
references
References 39 publications
3
123
1
41
Order By: Relevance
“…Acute limb ischemia (ALI) is an important consideration in patients with COVID-19 [ 26 ]. There have been over a dozen case reports and case series of ALI described in the literature [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%
“…Acute limb ischemia (ALI) is an important consideration in patients with COVID-19 [ 26 ]. There have been over a dozen case reports and case series of ALI described in the literature [ [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] ].…”
Section: Discussionmentioning
confidence: 99%
“…Potential causes of each dermatological findings Scarlet fever, measles, rubella, medication reaction, secondary syphilis, heat rash, leukemia, graft-versus-host disease Urticaria Allergic reaction, anaphylaxis, angioedema, autoimmune disease (e.g., systemic lupus erythematosus), hypereosinophilia, chronic urticaria, malignancy Vesicular Varicella zoster (i.e., chicken pox), herpes zoster (i.e., shingles), herpes simplex, Rhus dermatitis (e.g., poison ivy, poison oak, and poisonReproduced with permission from Elsevier LTD. The following original report is credited: Gottlieb et al97 DIC, disseminated intravascular coagulation.…”
mentioning
confidence: 99%
“…There have been multiple case reports and case series outlining dermatologic manifestations of COVID-19. The previously described exanthems include vesicular, pernio (chilblain)-like lesions, livedo reticularis, urticarial, petechial, and maculopapular [2,5,[7][8][9][10][11]. These viral exanthems have been described to occur throughout various stages of the disease and do not correlate well with severity of illness [4].…”
Section: Discussionmentioning
confidence: 99%
“…These viral exanthems have been described to occur throughout various stages of the disease and do not correlate well with severity of illness [4]. While many cases have reported dermatologic symptoms prior to respiratory symptoms, the majority of studies have suggested onset a few days after other symptoms [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation